LEXICAL DENSITY OF ENGLISH READING TEXTS FOR SENIOR HIGH SCHOOL - Nesia, Bersyebah Herljimsi; Ginting, Siti Aisah (Universitas Negeri Medan, 2014)
ABSTRACT This study deals with the lexical density especially the lexical items of English reading texts in the textbook for senior high school. The objectives of the study are to find out the lexical density especially the lexical items which formed in the reading texts of Look Ahead textbook and the type of genre which has the highest lexical density of the reading texts. This study was conducted by descriptive method with qualitative approach. The data of this research were the English reading texts of Look Ahead textbook for senior high school grade twelve published by Erlangga. The result of the analysis showed that: (1) The lexical items that formed in narrative texts are noun and verb, explanation texts are noun and verb, discussion texts are noun and verb, and review texts are noun, adjective, and verb. This means that narrative, explanation, and discussion texts are formed by two lexical items, they are noun and verb while review texts are formed by 3 lexical items, they are noun, adjective, and verb. (2) The lexical density of explanation texts are 58,42% an 52,05%, review texts are 55,73% and 53,51%, narrative texts are 48,96% and 43,97%, and discussion texts are 47,79% and 42,57%. The highest lexical density of the reading texts is the explanation text with percentage 58,42%. This meant that explanation text is the most difficult text to be comprehended in the textbook. It is suggested that further textbook writers to concern with the lexical density of the reading texts so that the textbook can be used and understood by the teacher and the students. Key words : Lexical Density, English Reading Texts